Application of Alkaline Pulping to Pruned Branches of Citrus limon from Sudan - KHIDER, Tarig; OMER, Safaa; ELZAKI, Osman; MOHIELDIN, Salaheldin; SHOMEINA, Suhair (Walailak Journal of Science and Technology (WJST), 2021)
This study aims to utilize the pruned branches of Citrus limon in pulping with alkaline pulping methods and to determine the suitability of guar gum to improve the strength properties of pulps and limitations of cutting trees for environmental issues and utilization of lemon branches as horticultural residues. These branches’ physical properties exhibited high medium density and very low percentages of bark to wood ratio. The whole chemical components of these raw materials indicated the suitability to a pulp with alkaline cooking methods. In addition, alkaline sulfite anthraquinone with methanol methods gave excellent screened yield (60.1 %), negligible rejects, bleachable Kappa number 19.5, and best strength properties, especially tensile and strengths. Alkaline sulfite with anthraquinone gave excellent screened yield with a small percentage of rejects and bleachable Kappa number. On the other hand, soda cooking produced pulps with acceptable yield (41.9 %), rejects (3 %), and suitable strengths. The soda anthraquinone pulping methods produced pulp with good yields (56 - 59.7 %). Obviously, anthraquinone’s effect in preserving carbohydrates, specifically hemicelluloses, increases the yields and strengths. Guar gum improved pulps’ physical properties when added during beating with (0.25 % on oven-dry Soda-AQ pulps). It clears Citrus limon branches’ suitability with an age of 2 years in cooking with all alkaline pulping methods applied.